Uso de redes sociales en el bienestar psicológico de jóvenes universitarios - Sánchez Alarcón, Cristopher Alexander (2023)
Social networks are digital platforms on which you can carry out several activities such as: connect, communicate, share information of our interest, or interact with other users. Psychological well-being refers to the state of mental and emotional health in people's lives, based on the balance and satisfaction of these areas; This can be composed by selfacceptance, autonomy, positive relationships, etc. Using social networks can bring benefits, but also bring situations that cause a negative impact on the psychological well-being of young university students such as excessive use and the generation of bad habits when using such platforms. In view of this problem, the objective of the research was to describe studies that show the use of social networks in the psychological well-being of young university students. To achieve this objective, a qualitative approach was used with a non-experimental, documentary, cross-sectional, descriptive, and bibliographic design. A thorough search was conducted in academic databases, journals, and academic search engines, where 7 studies published between 2018 and 2023 were selected. The results indicated that there is an excessive use of social networks by young university students, which can result in low levels of psychological well-being; Regarding the self-acceptance dimension, it was identified that it is characterized by feeling good about oneself and being self-competent, while the autonomy dimension is interpreted as decision making and being independent